Predictors of self-assessed likelihood of future drug use among Korean adults: the role of health beliefs and personality traits - Joon-Yong Yang; Minhye Kim; Aeree Sohn (BMC Public Health)
Abstract Substance use is a growing public health concern in South Korea. However, research on the predictive factors influencing future drug use remains limited. This study examined the self-assessed likelihood of future drug use in a sample of 3,000 Korean adults aged 19-59 years, focusing on health beliefs and personality traits as predictors. Using multiple regression analysis based on the health belief model (HBM) and selected personality traits, we explored how perceived susceptibility, self-efficacy, hope for the future, and sensation-seeking influence the likelihood of drug use. The results indicated that demographic factors such as sex, age, and income had limited predictive power. In contrast, past drug use and recent violence-related trauma significantly increased the likelihood of future drug use. Higher perceived susceptibility was associated with an increased likelihood of drug use, whereas greater self-efficacy was associated with a reduced likelihood. Among the personality traits, hope for the future was found to decrease, and sensation-seeking to increase the likelihood of drug use. This study underscores the need for interventions to enhance self-control and reduce drug accessibility. However, limitations such as reliance on self-reported data and a cross-sectional design suggest the need for longitudinal studies and culturally adapted measures in future research. These advances are crucial for validating and extending these findings, ultimately contributing to more effective drug prevention strategies.